Ankle and Hindfoot Kinematics of a Next Generation Total Ankle Replacement During Simulated Gait. Issue 3 (14th September 2018) - Sturnick, Daniel; Saito, Guilherme; Ellis, Scott; Demetracopoulos, Constantine
Category: Ankle Arthritis Introduction/Purpose: Total ankle arthroplasty (TAA) has developed as a viable treatment option for end-stage ankle arthritis. The primary benefit proposed with TAA is that allows for maintained motion of the ankle and hindfoot joint compared to the alternative option of an ankle arthrodesis. Consequently, recent TAA systems have focused on designs that advance kinematic function. Cadaveric gait simulation is a valuable tool for investigating the direct effects of surgical procedures and devices on foot and ankle biomechanics. The objective of this study was to assess whether a next generation TAA system permits normal ankle and hindfoot kinematics using cadaveric gait simulation. Methods: Ten mid-tibia cadaveric specimens were secured to a static mounting fixture relative a six-degree of freedom robotic platform to simulate gait in native-intact and TAA conditions. A force plate was moved relative to the stationary specimen through an inverse tibial kinematic path calculated from in vivo data while extrinsic tendons were actuated using physiologic loads (Figure 1A). Ankle and hindfoot kinematics were measured from reflective markers attached to bones via surgical pins. TAA was performed using a next generation, fixed bearing total ankle system by a fellowship trained foot and ankle surgeon using manufacturer described protocol (Cadence Total Ankle, Integra LifeSciences). Ankle and hindfoot joint kinematics were directly measured using the same kinematic inputs and muscle force as the intact condition. Non-parametric, bias-corrected bootstrapping was used to calculate 95% confidence intervals to compare motion between intact and total ankle replacement conditions. Results: Analyses revealed that no significant difference in average ankle or hindfoot joint kinematics were found between intact and TAA conditions (Figure 1B). This result was consistent in each the ankle, subtalar, and talonavicular joints, and in each plane of motion. Conclusion: This study found that normal kinematics were permitted on average by a next generation, fixed bearing TAA. This finding may indicate that improved functional outcomes following could be expected. However, increased variability and some characteristic differences in the paths of motion throughout stance were observed qualitatively. This report represents an initial analysis of preliminary data, future work will include further analyses and investigation on the influence of factors such as component position and alignment on outcomes. That said, the findings of this study are encouraging and may represent improved kinematic performance in new TAA designs.